Supplementation strategies for crossbred steers on Brachiaria brizantha pasture during the dry season: Effects on performance, intake, digestibility and ingestive behavior - Venicio Macedo Carvalho; Robério Rodrigues Silva; Tulio Otávio Jardim D`Almeida Lins; Daniele Soares Barroso; Tarcísio Ribeiro Rocha; João Wilian Dias da Silva; Marceliana da Conceição Santos; Kleves Vieira de Almeida; Ivanor Nunes do Prado (Acta Scientiarum. Animal Sciences, 2024)
Supplementation strategies have been studied to increase animal performance and the quality of meat. Thus, this study was carried out to evaluate the influence of different supplementation strategies on the performance, feed intake, digestibility and ingestive behaviour of crossbred steers on Brachiaria brizantha pasture, during the dry season. The experiment was performed in Bahia, Brazil, from August 2015 to January 2016, with a dry season of 203 days. Thirty-three crossbred steers with an average weight of 269.5 ± 41.8 kg were distributed in a completely randomised design with three treatments and 11 replicates per treatment. The results were analysed using an ANOVA and a Tukey test, with a 5% probability of error. The treatments were mineral salt with urea and the supplementation of protein based on the animals’ body weight (BW), as follows: 0.1 and 0.2% BW. There was no effect of supplementation strategy on the initial and final body weights. Supplementation strategies did not influence (p > 0.05) the variables related to the intake of total dry matter. There was an effect (p < 0.05) on the dry matter and crude protein digestibility coefficients. For ingestive behaviour, feed intake, grazing time and idle time tended to be altered by the supply strategies (p < 0.05), but rumination was not affected (p > 0.05) by the evaluated strategies. In conclusion, the supplementation strategies used during the dry season resulted in a similar performance; therefore, the adopted strategy can be chosen according to the economic and regional conditions of the production system. Thus, the strategy adopted could be chosen according to the economic and regional conditions of the production.